A farm-level perspective of the policy challenges for export diversification in Malawi: Example of the oilseeds and maize sectors - Johnson, Michael E.; Edelman, Brent; Kazembe, Cynthia (International Food Policy Research Institute, 2016)
The primary goal of the study is to investigate the potential to expand oilseeds, specifically soybeans,as an alternative commercialcrop to tobacco among Malawian farmers. A principal motivation for undertaking the study at the microeconomic level is to determine, in a theoretically consistent fashion, the type of policy and economic environment under which farmers begin to shift more of their scarce resources to oilseed production.The study aims to provide recommendations to a growing demand among policy makers and development partners for a greater diversification of exports and crop production systems of the majority smallholder farmers in Malawi. Using representative farm models, the study examinesthe potential for expanding production of soybeans among typical smallholder farming systems in Malawi. The results will help guide future policies and investments targeted at promoting greater crop diversification and incomes, in order to reduce poverty and malnutrition in Malawi. Given the amount of labor and land resources allocated to maize production for food security purposes, we also consider the policy challenges that emerge for crop diversification as a result